Sistem Pendukung Keputusan Rekomendasi Rumah Kost di Sekitar Kampus Menggunakan Metode SAW - Anik Oktavia Utami; Asyahri Hadi Nasyuha; Pulut Suryati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Yogyakarta, known as a student city, is a major destination for students from various regions in Indonesia to pursue higher education, including at the Universitas Teknologi Digital Indonesia (UTDI). The majority of UTDI students come from outside the city and therefore require temporary housing such as boarding houses (kost). However, selecting a suitable kost is often challenging due to the abundance of choices and various criteria that must be considered, such as distance to campus, rental price, facilities, safety, house rules, and cleanliness. This study aims to design and develop a Decision Support System (DSS) to provide the best boarding house recommendations around UTDI using the Simple Additive Weighting (SAW) method. SAW was chosen due to its capability to handle multi-criteria decision-making in a simple yet effective manner. Data collection methods include literature studies and questionnaires distributed to students. The evaluation process involved assigning weights to each criterion, followed by normalization and preference score calculation for each boarding house alternative. The final results show that the system successfully provides objective recommendations, with the highest-ranking boarding house being Kost Melati with a score of 1.798, followed by Kost Putri Raflesia (1.6), and Kost Ijo Putri (1.55). The developed DSS simplifies the previously manual and subjective kost selection process into a more structured and accurate system. In conclusion, the SAW method proves effective in supporting decision-making for kost selection around the UTDI campus. This research is expected to serve as a foundation for developing similar systems with more complex or combined methods for optimal results.